Effects of 2-Alkylamino-Substituted Dihydropyridines on Rabbit Jejunum: Effect of substituted dihydropyridines on jejunum - Hadizadeh, Farzin; Anaraki-Firooz, Bibi Fatemeh; Husain Taqvi, Syed Intasar (Iranian Journal of Pharmaceutical Sciences, 2005)
In order to investigate the effects of dimethylamino substituent at postion 2 of the dihydropyridine nucleus on its activity, dialkyl 1,4-dihydro-2-[2-dimethylamino) ethyl]-6-methyl-4-(1-benzyl-2-alkylthio-5-imidazolyl)-3,5-pyrdinedicarboxylates (6a-f) were synthesized. The synthesis was started from dialkyl 1,4-dihydro-2,6-dimethyl-4-(1-benzyl-2-alkylthio-5-imidazolyl)-3,5-pyridinedicarboxylates (5a-f) which their synthesis and effects as calcium channel antagonist on guinea-pig ileum has been reported previously. Rabbit jejunum was used to determine the relaxant or antagonistic activity of the synthesized compounds. Some of the compounds (6c-e) inhibited the spontaneous contractile activity of jejunum, dose-dependently and completely, while high-K+ contracted tissues were relaxed partially.